La contribución de la Gaceta de Madrid al desprestigio de Carlos IV y del Antiguo Régimen por la exaltación de Napoleón (1804-1808) - Larriba, Elisabel (Cuadernos de Historia Moderna, 2009)
The official Gaceta de Madrid played an important role in informing the public of current political issues beyond the Pyrenees. This study, which analyzes the numerous articles published about France between 1804 (the year when Napoleon acceded to the Imperial Throne) and 1808, shows how “gaceteros” (these journalists) –through the laudation of French Emperor– contributed to the discredit of Charles IV and the Ancient Regime during the turn-of-the-century and in the eve of the Peninsular War.
Keywords: Press; Gaceta de Madrid; Propaganda; Napoleon